2022
DOI: 10.31925/farmacia.2022.1.20
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dexmedetomidine on Clinical Efficacy of General Anesthesia and Stress Response in Children

Abstract: This study was aimed to explore the effect of dexmedetomidine (DEX) nose drops on paediatric general anaesthesia in the resuscitation room and its influence on children's postoperative stress. Sixty-eight children undergoing general anaesthesia were enrolled. They were randomly divided into two groups according to admission, with 34 cases in each group. Children in the experimental group received DEX at a 1µg/kg dose as nasal drops, combined with sevoflurane (SEV) anaesthesia. Children in the control group rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Subgroup analysis showed that intranasal dexmedetomidine significantly reduced the incidence of EA/ED compared to placebo or no drug (13 studies 4,8,16–22,27,28,30 ; OR 0.18, 95% CI 0.12–0.27; p = .0000; I 2 = 25.30%; Figure 2) and midazolam (7 studies 4,7–9,25,26,29 ; OR 0.36, 95% CI 0.19–0.71; p = .003; I 2 = 37.59%; Figure 2), whereas no significant differences were observed in the comparison between the intranasal dexmedetomidine and clonidine (1 study 24 ; OR 0.54, 95% CI 0.20–1.45; p = .220; I 2 = not applicable; Figure 2), esketamine (1 study 23 ; OR 0.47, 95% CI 0.17–1.33; p = .155; I 2 = not applicable; Figure 2), and ketamine (2 studies 7,10 ; OR 0.37, 95% CI 0.04–3.23; p = .365; I 2 = 61.42%; Figure 2).…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…Subgroup analysis showed that intranasal dexmedetomidine significantly reduced the incidence of EA/ED compared to placebo or no drug (13 studies 4,8,16–22,27,28,30 ; OR 0.18, 95% CI 0.12–0.27; p = .0000; I 2 = 25.30%; Figure 2) and midazolam (7 studies 4,7–9,25,26,29 ; OR 0.36, 95% CI 0.19–0.71; p = .003; I 2 = 37.59%; Figure 2), whereas no significant differences were observed in the comparison between the intranasal dexmedetomidine and clonidine (1 study 24 ; OR 0.54, 95% CI 0.20–1.45; p = .220; I 2 = not applicable; Figure 2), esketamine (1 study 23 ; OR 0.47, 95% CI 0.17–1.33; p = .155; I 2 = not applicable; Figure 2), and ketamine (2 studies 7,10 ; OR 0.37, 95% CI 0.04–3.23; p = .365; I 2 = 61.42%; Figure 2).…”
Section: Resultsmentioning
confidence: 95%
“…The incidence of EA/ED was 13.6% in the dexmedetomidine group and 33.2% in the control group. The pooled effect size revealed that dexmedetomidine administration significantly lowered the incidence of postoperative EA/ED in pediatric patients undergoing surgery under general anesthesia (20 studies 4,7–10,16–30 ; OR 0.25, 95% CI 0.18–0.34; p = .0000; I 2 = 37.74%; Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations